2011
DOI: 10.1093/jhered/esr041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2 Loci Associated with Development of Myxomatous Mitral Valve Disease in Cavalier King Charles Spaniels

Abstract: Myxomatous mitral valve disease (MMVD) is the most common heart disease in dogs. It is characterized by chronic progressive degenerative lesions of the mitral valve. The valve leaflets become thickened and prolapse into the left atrium resulting in mitral regurgitation (MR). MMVD is most prevalent in small to medium sized dog breeds, Cavalier King Charles Spaniels (CKCS) in particular. The onset of MMVD is highly age dependent, and at the age of 10 years, nearly all CKCS are affected. The incidence of a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 31 publications
2
74
0
7
Order By: Relevance
“…Myxomatous MV disease is most prevalent in small to medium-sized dog breeds. In King Charles cavalier spaniels, a GWAS identified loci associated with development of MVP in a 1.58 Mb region on CFA13 and a 1.68 Mb region on CFA14 40. More recently, a similar association study on whippet dogs identified new severity loci for MV degeneration on CFA15 and secondary loci of suggestive association on CFA2.…”
Section: Animal Models and Mvpmentioning
confidence: 99%
“…Myxomatous MV disease is most prevalent in small to medium-sized dog breeds. In King Charles cavalier spaniels, a GWAS identified loci associated with development of MVP in a 1.58 Mb region on CFA13 and a 1.68 Mb region on CFA14 40. More recently, a similar association study on whippet dogs identified new severity loci for MV degeneration on CFA15 and secondary loci of suggestive association on CFA2.…”
Section: Animal Models and Mvpmentioning
confidence: 99%
“…173 Clues might also be gathered from correlative studies with heritable canine MVP, a cause of severe heart failure and mortality. 178,179 …”
Section: Mitral Valve Prolapsementioning
confidence: 99%
“…A similar disease has a very high prevalence in Cavalier King Charles spaniels and GWAS conducted with 100 cases and 100 controls have recently identified two novel candidate regions. Studies are currently underway to identify the causative gene and mutation within the regions (Madsen et al, 2011).…”
Section: Myxomatous Mitral Valve Diseasementioning
confidence: 99%